2020
DOI: 10.33225/jbse/20.19.1020
|View full text |Cite
|
Sign up to set email alerts
|

Improvements in Teachers' Knowledge and Understanding of Basic Astronomy Concepts Through Didactic Games

Abstract: Literature review shows that many primary school teachers have poor understanding of basic astronomy contents. Therefore, the aim of the study was to introduce specific astronomical content to in-service primary school teachers through two didactic games, to evaluate the didactic games and the teachers’ knowledge and understanding before and after the implementation of the didactic games. The research included 24 in-service primary school teachers. The data were collected through the knowledge test (pre-post d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 42 publications
1
5
0
Order By: Relevance
“…Trundle et al (2007), however, summarize research by many authors on basic astronomical concepts and show that the content on Moon phases is too complex to be introduced to the lower grades of primary school, as students are developmentally unable to assimilate complex phenomena. In a sense, the present results confirm the above and underline the role of the qualified teacher to present the content with embodiment (Geršak et al, 2020;Susman & Pavlin, 2020). It is a similar situation to the 9th graders, e.g.…”
Section: Discussionsupporting
confidence: 90%
“…Trundle et al (2007), however, summarize research by many authors on basic astronomical concepts and show that the content on Moon phases is too complex to be introduced to the lower grades of primary school, as students are developmentally unable to assimilate complex phenomena. In a sense, the present results confirm the above and underline the role of the qualified teacher to present the content with embodiment (Geršak et al, 2020;Susman & Pavlin, 2020). It is a similar situation to the 9th graders, e.g.…”
Section: Discussionsupporting
confidence: 90%
“…Güneş' (2010) study on pre-service teachers showed a statistically significant relationship between academic achievement and self-efficacy belief in teaching astronomy. Moreover, Susman and Pavlin (2020) stated that in-service teachers expounded on how they felt uncomfortable teaching astronomy topics during the teacher training despite having worked on models of the solar system, moon phases, and eclipses. This result also supports the results from the current study.…”
Section: Conclusion Discussion and Recommendationsmentioning
confidence: 99%
“…Based on the students' short answers, it is not possible to deduce the extent to which they would like to continue with the given content, but in most cases it would be possible to incorporate the content into the existing curriculum and implement it outdoors. One exception is content on astronomy, especially on space and the stars, which always sparks the curiosity and interest of students of different ages (Susman & Pavlin, 2020). The students' responses do, however, show their interest in outdoor lessons.…”
Section: Rq6: Which Topics Are Of Interest To Students With Regard To...mentioning
confidence: 96%